Role of TRPV1 ion channel in cervical squamous cell carcinoma genesis - Wang, Zhenming; Dong, Junhong; Tian, Wenxiu; Qiao, Sen; Wang, Hongmei (Frontiers in Molecular Biosciences, 2022)
The transient receptor potential (TRP) family is a widely expressed superfamily of ion channels that regulate intracellular Ca2+ homeostasis and signal transduction. Abnormal expression of TRPV1 is closely related to malignant tumors of the female reproductive system such as breast, ovarian, cervical and endometrial cancers. In this study, we found a significant reduction of TRPV1 expression in cervical squamous cell carcinoma and this expression is inversely association with the risk of cervical squamous cell carcinoma. Furthermore, TRPV1 is involved in cell differentiation, iron death, inflammatory response, and metabolic regulation in cervical squamous cell carcinoma. Meanwhile TRPV1 is positively correlated with T cells and negatively associated with macrophages, indicating that TRPV is associated with tumor cell immunity. Therefore, TRPV1 may be a potential marker of cervical cancer and a promising anti-cancer drug candidate.